Analysis on the escape phenomenon of oil mist from turbine lower guide bearing based on VOF model. (November 2021) - Pang, Jiayang; Liu, Huizi; Liu, Xiaobing; Ren, Minghui; Zhang, Pan; Yu, Zhishun
To analyze the cause and mechanism of oil mist escaping from the lower guide bearing during the operation of a turbine, the oil-gas mixture in the lower guide bearing was numerically simulated by using the VOF two-phase flow model and the SST turbulence model. The influences of different sealing clearances and speeds on the flow field and the oil-gas distribution in the oil tank were studied, and the escaping characteristics of oil mist were analyzed. The results show that increasing the clearance of the labyrinth seal will reduce the pressure difference between the inside and outside of the oil tank and reduce the driving force for the escape of the oil mist. However, increasing the clearance will increase the turbulence of the flow field, the number and volume of bubbles in the lubricating oil, which will lead to the uneven distribution of oil and gas and reduce the motion stability of the lower guide bearing. The change of speed will affect the normal use of the shaft-collar pump. High speed will aggravate the generation of bubbles in the oil tank and increase the possibility of cavitation in the lower guide bearing structure. In engineering practices, it is necessary to comprehensively consider factors such as oil mist escape phenomenon, economic benefits, process manufacturing and assembly, and adopt the lower guide bearing structure with a suitable labyrinth seal clearance.